2012
DOI: 10.1159/000342139
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Auditory Training Using the Auditory Brainstem Response to Complex Sounds: Auditory Processing Disorder and Specific Language Impairment

Abstract: Objectives: This study verified the efficacy of a formal auditory training (AT) program in children with hearing and language disorders using the auditory brainstem response to complex sounds (c-ABR) with and without background noise. Patients and Methods: Thirty children (7–13 years) were distributed into four groups: typical development (TD: n = 7), auditory processing disorder (APD: n = 9) and specific language disorder (SLIa: n = 6, and SLIb: n = 8). All children underwent behavioral assessment of auditory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 83 publications
3
47
0
10
Order By: Relevance
“…Similar results were also observed in a previous study (7) , which observed the responses of children with APD, and demonstrated that 80% of them had abnormal speech-evoked ABR . These data are in accordance with studies that showed a major relationship between deficits in speech-evoked ABR and in auditory perception (6)(7)(8) , and that demonstrated improved speech-evoked ABR response after auditory stimulation (5,9,11) . Based on the observations of the present study, and on the current knowledge about speech-evoked ABR, it is possible to discuss some clinical applications of this potential.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Similar results were also observed in a previous study (7) , which observed the responses of children with APD, and demonstrated that 80% of them had abnormal speech-evoked ABR . These data are in accordance with studies that showed a major relationship between deficits in speech-evoked ABR and in auditory perception (6)(7)(8) , and that demonstrated improved speech-evoked ABR response after auditory stimulation (5,9,11) . Based on the observations of the present study, and on the current knowledge about speech-evoked ABR, it is possible to discuss some clinical applications of this potential.…”
Section: Discussionsupporting
confidence: 92%
“…In Brazil, speechevoked ABR has been studied for approximately 10 years, and has only a few publications (2)(3)(4)(5)(6) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the other five papers, one investigated the effects of formal auditory training on language skills (18), and the other four investigated the effects on auditory skills (20-23). Megale and Schochat (18) investigated the effectiveness of formal auditory training in elderly hearing aid users and reported effects similar to those of the Gil & Iorio study (19).…”
Section: Resultsmentioning
confidence: 99%
“…The suffering of students with learning difficulties appears in their perceptions; in order to address these difficulties, it is necessary to develop special auditory training programs for them, as they perceive things differently. It is wrong to put pressure on them because it makes them feel that they have failed and are unable to perceive and discriminate, as they are in need of special means to help them with their learning (Filippini, et al 2013). Perceptual processes are considered prerequisites to learning to read, because developmental learning difficulties represented in the synthesis of sounds (auditory perception) are one of the main reasons that prevent a child from learning to read (Herrmann, 2012; Al-Bashtawy et al, 2014).…”
Section: Social Difficultiesmentioning
confidence: 99%